Application Mass Spectrum Method in Determination Compound Bioactive of The Essential Oil from Leaves and Stems of Clove (Syzigium aromaticum) - Rifai, Akhmad; Riyadi, Nur Amin (Politeknik Negeri Ujung Pandang, 2021)
The essential oil from leaves and stems of clove (Syzigium Aromaticum) growing in Siwa (South Sulawesi, Indonesia), was obtained by hydrodistillation and gas chromatography-mass spectrometry (GC-MS) was used to identify the constituent of the sample. There were five most compounds bioactive contained in the clove oil of the leaves and stems, namely eugenol,Â b-caryophyllene, 1,4,7- cycloundecatriene-1,5,9,9 tetramethyl, caryophyllene oxide, and cadinene. The eugenol compound, which is contained in the stems is 55.83% bigger than the leaves, which is 45.3%. But on the contrary, other compounds in the leaves areÂ b-caryophyllene (25.57%), 1,4,7- cycloundecatriene-1,5,9,9 tetramethyl (8.65%), caryophyllene oxide (4.64%) and cadinene (2.31%) greater than the other compounds in the stems, namelyÂ b-caryophyllene (19.72%), 1,4,7- cycloundecatriene-1,5,9,9 tetramethyl (4.38%), caryophyllene oxide (3.48%) and cadinene (0.5%). Eugenol is the major constituent of the clove oil that can be used in pharmacology as antivirus, antimicrobial, antiseptic, and industry of perfume.